Did the COVID-19 lockdown result in a delay of colorectal cancer presentation and outcomes? A single centre review - Lee, Tsinrong (2022)
Purpose: The COVID-19 pandemic and resultant lockdown measures potentially delay management of non-communicable, life-limiting diseases like colorectal cancer (CRC) through avoidance of healthcare facilities by the public and diversion of resources within healthcare systems. This study aims to evaluate the impact of Singapore’s “Circuit Breaker (CB)” lockdown measures on CRC disease presentation and short-term surgical outcomes, while comparing Singapore’s approach against other countries which employed similar lockdown measures. Methods: Patients whose initial diagnosis of CRC was made within the 6-month pre-CB (6/10/19–6/4/20) (“pre-CB group”) and post-CB (7/4/20–7/10/20) (“post-CB group”) period were enrolled retrospectively. The groups were compared based on severity of disease on presentation and short-term operative outcomes. Results: In total, 105 patients diagnosed with CRC were enrolled in this study. When comparing pre-CB and post-CB groups, there was no significant difference in stage of CRC on presentation (p=0.850). There was also no increase in need for emergent operations (p=0.367). For patients who had undergone an operation, postoperative morbidity was not significantly higher in the post-CB group (p=0.201). Both groups of patients had similar length of stay in the hospital (p=0.438). Conclusion: Unlike similar high-income countries, Singapore did not see later stage disease on presentation and poorer operative outcomes after lockdown measures. Possible reasons include lesser healthcare avoidance behaviours amongst Singaporeans, and adequate preparation of resources and contingency plans formed by hospitals after previous pandemics.